(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Home-based rehabilitation post-stroke can help to improve the recovery of upper limb motor function, increase patient motivation for training, lower rehabilitation costs, and optimize post-stroke care for clinical staff. Rehabilitation in acute and chronic post-stroke phases with task-specific, repetitive training has been shown to improve upper limb function. Rehabilitation technology such as robotic devices can provide such physical training and facilitate consistent rehabilitation means. However, the large dimensions of such devices, high costs, and various technical aspects are factors that can limit usage only in rehabilitation facilities. This paper presents the design of a lightweight and fully portable active orthosis that provides passive mobilization of the elbow and has an innovative mechanism for supination and pronation of the forearm. A 3D model was constructed, considering the biomechanical requirements of the joints and overall feasibility for home use. 3D scanning and printing were used to develop and produce the device. The usability of the active orthosis was evaluated on 5 healthy volunteers using the System Usability Scale, which revealed very good results. The active orthosis presents easy set-up and operation, making it an excellent tool for at-home rehabilitation.